Professor Pigou's Method for Measuring Elasticities of Demand From Budgetary Data - Friedman, Milton (Quarterly Journal of Economics, 1935)
Journal Article Professor Pigou's Method for Measuring Elasticities of Demand from Budgetary Data Get access Milton Friedman Milton Friedman University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 50, Issue 1, November 1935, Pages 151–163, https://doi.org/10.2307/1882346 Published: 01 November 1935